Mechanism of Electroacupuncture Analgesia on Nicotine Withdrawal-Induced Hyperalgesia in a Rat Model. (29th August 2022) - Alfonso-Rodriguez, Jeimy; Wang, Shuju; Zeng, Xiaoling; Candiotti, Keith A.; Zhang, Yanping
Abstract : Purpose . This study aimed to investigate the analgesic effect and mechanism of electroacupuncture (EA) in nicotine withdrawal-induced hyperalgesia rats. Methods . Behavioral testing was conducted twice a week for 7 weeks during nicotine administration using von Frey filaments. Electroacupuncture at the bilateral "Zusanli" and "Taichong" points was applied daily for 3 days during nicotine withdrawal. Western blot analysis and immunohistology were used to determine expression levels of pain-related factors in the spinal cord and midbrain periaqueductal gray (PAG). Results . Behavioral tests showed that electroacupuncture had a significant analgesic effect on nicotine withdrawal-induced hyperalgesic rats. Western blot results demonstrated that, in hyperalgesic rats, the expressions of nicotinic acetylcholine receptors (subunits: nAChR α 7, α 4, or β 2) decreased in the spinal cord, nAChR α 7, and β 2 decreased in PAG. The proinflammatory factor cyclooxygenase 2 (COX2) and the activated microglia (ionized calcium-binding adaptor molecule 1, Iba1 positive cells) increased in the spinal cord and PAG compared to controls. After electroacupuncture treatment, nAChR α 7 and nAChR β 2 expressions increased significantly, and COX2 and Iba1 expressions decreased in the spinal cord. Compared with the nonelectroacupuncture nicotine withdrawal group, electroacupuncture stimulation increased the expression of nAChR α 7 and nAChR α 4 in the PAG of rats with electroacupuncture. Immunohistochemical results confirmed that electroacupuncture reversed nicotine withdrawal-induced changes in nAChR α 7 positive neurons and Iba1-positive microglia in the dorsal horn of the spinal cord. Conclusion . Electroacupuncture treatment has an analgesic effect on nicotine withdrawal-induced pain in nicotine-dependent rats. The mechanism of analgesia of the electroacupuncture treatment relates to the increased expression of nAChR α 7 and nAChR β 2 proteins in the spinal cord, nAChR α 7 in the PAG, and decreased expression of Iba1 and COX2 protein in the spinal cord.